G-protein coupled receptors of the renin-angiotensin system: new targets against breast cancer? - Rodrigues-Ferreira, Sylvie; Nahmias, Clara (Frontiers in Pharmacology, 2015)
G-protein coupled receptors (GPCRs) constitute the largest family of membrane receptors, with high potential for drug discovery. These receptors can be activated by a panel of different ligands including ions, hormones, small molecules and vasoactive peptides. Among those, angiotensins (angiotensin II and angiotensin 1-7) are the major biologically active products of the classical and alternative Renin-Angiotensin System (RAS). These peptides bind and activate three different subtypes of GPCRs, namely AT1, AT2 and Mas receptors, to regulate cardiovascular functions. Over the past decade, the contribution of several RAS components in tumorigenesis has emerged as a novel important concept, Angiotensin II being considered as harmful and Angiotensin 1-7 as protective against cancer. Development of selective ligands targeting each RAS receptor may provide novel and efficient targeted therapeutic strategies against cancer. In this review, we focus on breast cancer to summarize current knowledge on angiotensin receptors (AT1, AT2, and Mas), and discuss the potential use of angiotensin receptor agonists and antagonists in clinics.